Penyisihan Nutrien dengan Material Zeolit dan Karbon Aktif dalam Teknologi Sediment Capping Studi Kasus Danau Batur Bali - Almalia, Rosalina; Soewondno, Prayatni; Sunaryani, Astried (Jurnal Serambi Engineering, 2026)
Lake Batur is one of the national priority lakes that is experiencing pollution pressure due to anthropogenic activities. Nitrogen in the form of ammonium (NH₄) and phosphorus in the form of orthophosphate (PO₄) at high levels cause eutrophication. One of the technologies used to address eutrophication in Lake Batur is sediment capping technology. Sediment capping involves covering the sediment surface with a capping layer of adsorbent material that must effectively adsorb nutrients, prevent their release back into the water, and remain stable under lake environmental conditions. Therefore, adsorbent materials that are selective, environmentally friendly, and easily obtainable especially in the local context of Lake Batur are required. This study aims to determine the capability of zeolite and activated carbon as capping materials through laboratory experiments. The parameters tested include the adsorption efficiency of zeolite and carbon in removing ammonium and orthophosphate under various conditions such as pH, dosage, and equilibrium isotherms. The results of the study show that both materials have potential as capping materials but zeolite is more recommended for nutrient management in Lake Batur.